MANGO-SEED EXTRACT AND SULPHITES AS PROMOTERS OF COLOR AND BIOACTIVE COMPOUNDS RETENTION DURING TRAY DRYING OF MANGO SLICES - JIMÉNEZ-DURÁN, A.; SANTOS-SÁNCHEZ, N.F.; HERNÁNDEZ-CARLOS, B.; JULIANI, H.R.; SALAS-CORONADO, R. (Italian Journal of Food Science, 2020)
The study objective was to evaluate effect of mango-seed extract alone or in combination with sodium metabisulphite on the content of vitamin C, free phenols, six phenols compounds, and total carotenes, and color in mango slices dried at 60ºC until 15% moisture. From drying curves were calculated effective diffusivities [1.17-1.35x10-9 m2•s-1] and drying rate constants [1.53±0.90x10-3-2.27±0.80x10-3] using Midilli’s model. Results showed that combination of mango-seed extract with sodium metabisulphite has an important role in retention of vitamin C and carotenes, and an enrichment of phenolic compounds was found in dried mango slices.